Psychosocial problems of family caregivers of palliative care patients and their spiritual coping styles - Özdemir, Fatıma; Doğan, Sibel; Atayoğlu, Ali Timuçin (Wiley, 2020)
Purpose The aim of the study was to examine the psychosocial problems and spiritual coping styles of the family caregivers related to patients receiving palliative care.Design and Methods The research sample consisted of 76 family caregivers related to palliative care patients. The data collection method used were questionnaire forms. The two forms used were Hospital Anxiety Depression Scale and Religious Coping Methods Scale.Findings The mean anxiety score of the participants was 10.86 +/- 4.30, mean depression score was 9.38 +/- 3.66, mean positive coping scale score was 25.31 +/- 3.85, and mean negative coping scale score was 10.32 +/- 3.38.Practice Implications Healthcare professionals involved in palliative care are encouraged to evaluate the spiritual experiences of family caregiver to support their wellbeing.
Keywords: Anxiety; Depression; Holistic Health; Palliative Care; Spiritual Coping